STRATEGI PENGEMBANGAN USAHATANI SAYURAN DI KELURAHAN KALAMPANGAN KECAMATAN SABANGAU KOTA PALANGKA RAYA - Remi Marsinta Lingga; Abdul Mukti; Jhon Wardie (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
This study aims to identify internal and external factors that affect the management of vegetable farming, development strategies, and priorities so that it is expected to be useful in developing the management of this farm. Qualitative data were compiled from informants consisting of selected key informants and local respondents selected randomly from local farmers. This data is analyzed descriptively and quantized by using SWOT method and by using QSPM (Quantitative Strategic Planning Matrix) matrix. The results showed that the development of vegetable farming is influenced by the availability of large enough land but less fertile / peat. The trend of market demand tends to increase but there are fewer local and external competitors; Strategy analysis through SWOT matrix resulted seven alternative strategies that is optimizing the potential of land owned by opening access road to vegetable farming area, and expanding vegetable planting area; follow technological developments in vegetable farming, especially organic vegetables, and develop business with the utilization of capital assistance; increase production and quality of crops; to make peatlands suitable for agricultural land and to minimize costs. Priority strategies that can be applied in the development of vegetable farming based on QSPM are: the means of production and agricultural tools available locally, the distance of the competitor's location with the vegetable market further, and the majority of the population work as farmers (no shortage of labor).